2013
DOI: 10.1371/journal.pone.0081906
|View full text |Cite
|
Sign up to set email alerts
|

Oral Leptin Treatment in Suckling Rats Ameliorates Detrimental Effects in Hypothalamic Structure and Function Caused by Maternal Caloric Restriction during Gestation

Abstract: A poor prenatal environment brings about perturbations in leptin surge and hypothalamic circuitry that program impaired ability to regulate energy homeostasis in adulthood. Here, using a rat model of moderate maternal caloric restriction during gestation, we aimed to investigate whether leptin supplementation with physiological doses throughout lactation is able to ameliorate the adverse developmental malprogramming effects exerted in offspring hypothalamus structure and function. Three groups of male and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 43 publications
8
39
0
Order By: Relevance
“…Another possibility is that the number of NPY neurons differs between males and females and that such differences cause discrepancies in NPY mRNA expression under fasted conditions. Konieczna et al counted the number of NPY‐positive neurons in the arcuate nucleus, an area of the hypothalamus containing abundant NPY‐positive neurons, in pre‐pubertal rats (Konieczna et al, 2013) and found that the female rats seemed to possess fewer NPY‐positive neurons than the males; however, they did not confirm this using statistical methods. On the other hand, in the present study under the fed conditions NPY mRNA expression did not differ between males and females, regardless of whether it was normalized to the expression level of GAPDH.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the number of NPY neurons differs between males and females and that such differences cause discrepancies in NPY mRNA expression under fasted conditions. Konieczna et al counted the number of NPY‐positive neurons in the arcuate nucleus, an area of the hypothalamus containing abundant NPY‐positive neurons, in pre‐pubertal rats (Konieczna et al, 2013) and found that the female rats seemed to possess fewer NPY‐positive neurons than the males; however, they did not confirm this using statistical methods. On the other hand, in the present study under the fed conditions NPY mRNA expression did not differ between males and females, regardless of whether it was normalized to the expression level of GAPDH.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the increased milk intake in PN14 CR L versus CR S . More recently, oral administration of leptin throughout the postnatal period after only a modest 20% restriction of calories during conception (E1‐E12 days) led to recovery of the hypothalamic structure and neuropeptides at PN25 (Konieczna et al, ). In our present study, this effect of exogenous leptin over a shorter postnatal period (PN2‐PN8) following late gestational calorie restriction (E11 to E21) on hypothalamic NPY and AgRP is mediated by enhanced post‐ObRb (Cottrell et al, ) signaling seen as increased pSTAT3 and reduced PTP1B and SOCS3 (both inhibitors of leptin signaling).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-NPY has also been shown to react with NPY-containing neurons in frozen rat brain sections following 4% paraformaldehyde perfusion fixation. This antibody has been used in several studies looking at the effects of diet manipulation or treatment with feeding-regulatory peptides such as orexins, leptin or ghrelin on NPY immunohistochemical expression (for example: Cheunsuang & Morris 2005, Kobelt et al 2008, Garcia et al 2010, Li et al 2012, Konieczna et al 2013, Pekala et al 2011.…”
Section: Immunohistochemistrymentioning
confidence: 99%